MODERATISM OF SYAH WALIYULLAH AD-DIHLAWI (Analysis of His Thoughts in Kitab Al-Inshaf fi Bayani Asbab al-Ikhtilaf) - Achmad Subkhan (TAWASUT, 2021)
The difference of opinion on the issue of fiqh has occurred since generations of companions, tabi'in and priests of madhhab. The differences that occur in each generation have different causes. One of the conflicts that occurred between Muslims was triggered by differences of opinion on issues of Islamic law. This conflict intensified after the fourth century Hijriyah. In order for conflicts to be minimized, a moderate attitude of Muslims is needed by knowing the causes of these differences and the attitudes of previous scholars in dealing with them. The type of this research is library research, using descriptive methods and qualitative approaches. As for revealing information used content analysis techniques (content analysis). This study reveals the moderateism of Syah Waliyullah ad-Dihlawi which is shown through his work entitled al-Inshaf fi Bayan Asbab al-Iktilaf. Ad-Dihlawi mapped the causes of differences of opinion and presented them objectively. Ad-Dihlawi also revealed a history of the attitude of friends, tabi'in and priests of madhhab in dealing with differences of opinion. According to him, in dealing with differences, it is necessary to imitate the attitude exemplified by companions, tabi'in and priests of madhhab